(untitled) (Revista LIDER, 2020)
This paper aims to reflect on the relationship between integrated urbanization projects and the model of planning and management of urban policy. Empirically it was conducted a case study in the community of Passo da Pátria, Cidade Alta neighborhood, in the city of Natal-RN/Brazil in the 2013-2014 period. The experience reveals that such projects on their own specificity, carry a high level of complexity, just by combining several obstacles that must be solved through the integration of participatory policies.